P17 The clinicopathological characteristics and prognosis of cervical stump carcinoma: a retrospective analysis. (1st November 2019) - Cheng, J; Wu, X; Wen, H
Abstract : Introduction/Background: Carcinoma of cervical stump rarely happens to patients who underwent supracervical hysterectomy (SCH) previously. It is difficult to be treated with brachytherapy because of the pelvic anatomic modification, so most patients are treated with surgery. This study aimed to evaluate clinicopathological characteristics and prognosis of cervical stump carcinoma compared to matched controls with ordinary cervical carcinoma. Methodology: In this retrospective analysis, 96 consecutive cervical stump carcinoma cases who received radical surgery in Fudan University Shanghai Cancer Center between Apr 2006 and Feb 2014. Three controls to each case were randomly selected from ordinary cervical carcinoma using propensity score matching analysis (matched to FIGO stage, age, diagnostic year, ECOG performance status, menopause status, childbirth status and histologic type). The clinicopathological characteristics and follow-up data were analyzed and compared between controls and cases. Results: The average age of cervical stump carcinoma was 50.7 years old and pathological examination showed 86.5% of squamous cell carcinoma, 10.4% of adenocarcinoma and 3.1% of adenosquamous carcinoma. There were 63.5% cases in FIGO stage I, 35.4% cases in stage II and 1% cases in stage IIIa. The significant prognostic prognostic factors included FIGO stage, tumor size and lymph node metastasis. Compared to controls, less patients with cervical stump carcinoma had stromal invasion >1/2 (p=0. 001) and received adjuvant therapy(p=0.009). Otherwise, there was no statistical difference between cervical stump carcinoma and ordinary cervical carcinoma in 5-years OS (84.6% vs 85.5%, p=0.750) and RFS (85.2% vs 81.4%, p=0.389). Conclusion: There are no statistical difference in survival between Cervical stump carcinoma and ordinary cervical carcinoma. Disclosure: Nothing to disclose.